Conducting Other People's Affairs Without a Power of Attorney in a Pandemic: Poland and Ukraine - Mysiak, Piotr; Мисяк, Петр; Зубар, Володимир Михайлович; Зубар, В. М.; Зубарь, Владимир Михайлович; Zubar, Volodymyr M.; Пеструєв, Дмитро Миколайович; Пеструєв, Д. М.; Пеструев, Дмитрий Николаевич; Pestruiev, Dmytro M. (Hemisferios University, 2020)
The Covid-19 coronavirus pandemic has caused changes in all areas of human life. The field of law is no exception to this list. In particular, the issues of conducting other people’s affairs without a power of attorney have become especially relevant, as social distancing and restrictions on social activity have led to a significant increase in the practical need for the application of this legal institution. The significance of this study is also important in connection with the comparative analysis of the normative aspect and the practical measurement of the application of the institute of conducting other people’s affairs without a power of attorney in Ukraine and Poland. These two countries are comparable in territory, number of citizens, legal tradition, but Poland has become member of the European Union, while Ukraine has remained on the sidelines of European civilization. The dialectical method, the method of comparative analysis and system analysis were chosen as the methodological basis of the research. The authors of the article concluded that institute of conducting other people’s affairs without a power of attorney is characterized by an increased level of social utility. In such cases, the one who protects the interests of others without a power of attorney, as a rule, acts not only in the interests of the individual but also in the interests of the society. Thus, it helps to protect single people, the elderly ones, disabled individuals and other groups which are socially unprotected and thus prevent the pandemic spread.

Пандемія коронавірусу Covid-19 спричинила зміни у всіх сферах життя людини. Сфера права не є винятком із цього списку. Зокрема, особливої ​​актуальності набули питання ведення чужих справ без довіреності, оскільки соціальне дистанціювання та обмеження соціальної активності призвели до значного зростання практичної потреби у застосуванні цього правового інституту. Важливість даного дослідження є також у зв’язку з порівняльним аналізом нормативного аспекту та практичним виміром застосування інституту ведення чужих справ без довіреності в Україні та Польщі. Ці дві країни порівняні за територією, кількістю громадян, правовою традицією, але Польща стала членом Європейського Союзу, а Україна залишилася на узбіччі європейської цивілізації. Методологічною основою дослідження було обрано діалектичний метод, метод порівняльного аналізу та системного аналізу. Автори статті дійшли висновку, що інститут ведення чужих справ без довіреності характеризується підвищеним рівнем суспільної корисності. У таких випадках той, хто захищає інтереси інших осіб без довіреності, як правило, діє не лише в інтересах особи, а й в інтересах суспільства. Таким чином, це допомагає захистити одиноких людей, літніх людей, інвалідів та інших соціально незахищених груп і таким чином запобігти поширенню пандемії.
Mysiak P. Conducting Other People's Affairs Without a Power of Attorney in a Pandemic: Poland and Ukraine / P. Mysiak, V. Zubar, D. Pestruiev // Ius Humani. Law Journal. - Vol. 9. - Iss. 2. - Hemisferios University, 2020. – P. 87-110.
Keywords: negotiorum gestio; conducting other people’s affairs without a power of attorney; legal altruism; quarantine; coronavirus; дія в чужому інтересі без доручення; ведення чужих справ без довіреності; правовий альтруїзм; карантин; коронавірус; Research Subject Categories::LAW/JURISPRUDENCE